The Crystal Structure of the C-Terminal Domain of the Salmonella enterica PduO Protein: An Old Fold with a New Heme-Binding Mode - Ortiz de Orué Lucana, Darío; Hickey, Neal; Hensel, Michael; Klare, Johann P.; Geremia, Silvano; Tiufiakova, Tatiana; Torda, Andrew E. (Frontiers in Microbiology, 2016)
The two-domain protein PduO, involved in 1,2-propanediol utilization in the pathogenic Gram-negative bacterium Salmonella enterica is an ATP:Cob(I)alamin adenosyltransferase, but this is a function of the N terminal domain alone. The role of its C-terminal domain (PduOC) is, however, unknown. In this study, comparative growth assays with a set of Salmonella mutant strains showed that this domain is necessary for effective in vivo catabolism of 1,2-propanediol. It was also shown that isolated, recombinantly-expressed PduOC binds heme in vivo. The structure of PduOC co-crystallised with heme was solved (1.9 Å resolution) showing an octameric assembly with four heme moieities. The four heme groups are highly solvent-exposed and the heme iron is hexa-coordinated with bis-His ligation by histidines from different monomers. Static light scattering confirmed the octameric assembly in solution, but a mutation of the heme-coordinating histidine caused dissociation into dimers. Isothermal titration calorimetry using the PduOC apoprotein showed strong heme binding (Kd = 1.6 × 10-7 M). Biochemical experiments showed that the absence of the C terminal domain in PduO did not affect adenosyltransferase activity in vitro. The evidence suggests that PduOC:heme plays an important role in the set of cobalamin transformations required for effective catabolism of 1,2-propanediol. Salmonella PduO is one of the rare proteins which binds the redox-active metabolites heme and cobalamin, and the heme-binding mode of the C-terminal domain differs from that in other members of this protein family.